Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan Pada PT. Inatel Nusantara - Ayu Nur Aimi; Kadek Dewi Padnyawati (UNHI Press, 2023)
Company performance is one measure of success at the implementation on financial functions. Weak corporate governance is characterized with selfish action which do not include interests of investor, thereby making investor' expectations fall about returns at investment which has been invested. This studies aims on obtaining empirical evidences regarding effect of good corporate governances at company performances at PT. Nusantara Intel. The research population is 140 employees. Sampling using purposive method involving 40 employees. Data collected through observation, interview also questionnaire. Simple regression analysis is used. Result shown that good corporate governances has positive significant effects at company performance